''A science to it'': flexible time and flexible subjectivity in the digital workplace. (1st July 2013) - Frederick Pitts
Abstract : This paper details a research project exploring how working time is structured in the digital industries in the UK, drawing on a case study of a Bristol web enterprise situated in the 'Silicon Gorge'' high-tech hub, and incorporating ethnography, interviews, observation and time diaries. The role of the Internet in blurring the demarcation between paid and unpaid labour features prominently in the work patterns of the research participants. The culture of flexibility that abounds in the case study company harnesses the subjectivities and selves of individual employees to a cycle of ''project time'' centred around specific tasks and deadlines, completely divorced from recognition of an individual's contribution based on traditional temporal measures.